Motoric mechanism with problem based learning: impact on students’ higher order thinking skill - Siti Nabilah; Yenny Anwar; R Riyanto (Universitas Negeri Jakarta, 2019)
This study aims to determine the effect of Problem Based Learning (PBL) model on higher-order thinking skills (HOTS) of Eleventh-grade students on motion system material in SMA Negeri 1 Indralaya Utara. The research method used was Quasi-Experimental with the research design of Non-equivalent Control Group Design. The sampling method used was Saturated Sampling Techniques. The instruments of data collection are HOTS test questions in the form of multiple choices with five answer choices in twenty-five questions. Observation instrument of learning implementation used Checklist with twelve observation items. The response instruments of students use questionnaires with a Likert scale. HOTS data were tested using the Mann-Whitney test, and then the learning implementation data and students’ response data were analyzed descriptively. This data processing uses SPSS twenty-three. Based on the results of the hypothesis test, the sig value is 0.00 (sig <0.05), which shows an effect studied was significant. The implementation of learning has Good Category, while the response of students has very good and good categories of the two types of the response of students measured. Based on the hypothesis test results can be concluded that the PBL’s model can significantly influence higher-order thinking skills of Eleventh-grade students on motion system material in SMA Negeri 1 Indralaya Utara.